2021
DOI: 10.4314/tjpr.v20i11.16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sargassum plagiophyllum extract pretreatment on tissue histology of constipated mice

Abstract: Purpose: To evaluate the toxicity of the dried seaweed, Sargassum plagiophyllum, extract (SPE) pretreatment in constipated mice.Methods: The dried seaweed powder was mixed with distilled water and extracted by autoclave at 121°C. Antioxidant activity of the extract was determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Human normal colon cells were pretreated with SPE at 0 - 100 μg/mL for 24 h before challenging them with 100 μM hydrogen peroxide (H2O2). Intracellular reactive oxygen species (ROS) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This result indicates that Na + absorption in the distal colon reduced, and fecal water content therefore increased. In a recent study, it was found that goblet cell numbers on the villi of ileum increased in constipated mice pretreated with SPE [ 34 ]. This finding implied that mucus secretion in the ileum might also have increased, which supports our finding that fecal water content increased in constipated mice supplemented with SPE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result indicates that Na + absorption in the distal colon reduced, and fecal water content therefore increased. In a recent study, it was found that goblet cell numbers on the villi of ileum increased in constipated mice pretreated with SPE [ 34 ]. This finding implied that mucus secretion in the ileum might also have increased, which supports our finding that fecal water content increased in constipated mice supplemented with SPE.…”
Section: Discussionmentioning
confidence: 99%
“…To prepare SPE and lactulose solutions for daily administration, SPE powder was freshly dissolved in distilled water. In all mice, except mice in the normal control group, constipation was induced by injection of 5 mg/kg loperamide (Lop) on day 12, day 13, and day 14 [ 34 , 36 ]. The body weight of each mouse was recorded every day.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation